99mTc-TRODAT-1 SPECT as a Potential Neuroimaging Biomarker in Patients With Restless Legs Syndrome. (January 2016) - Lin, Chun-Chieh; Fan, Yu-Ming; Lin, Guan-Yu; Yang, Fu-Chi; Cheng, Chun-An; Lu, Kuo-Cheng; Lin, Jen-Cheng; Lee, Jiunn-Tay
Abstract : Background: Restless legs syndrome (RLS) is a neurological sensory motor disorder of which pathophysiology remains sketchy. The present study was aimed to determine the diagnostic accuracy and potential of SPECT-TRODAT imaging in discriminating patients with RLS from normal individuals. Patients and Methods: A total of 34 subjects, 22 diagnosed with RLS and 12 classified as normal, were enrolled. Brain SPECT images were acquired 180 minutes after IV injection of 740 to 925 MBq (20–25 mCi) 99m Tc-TRODAT-1 using a double-headed γ-camera equipped with high-resolution fan-beam collimators. Regions of interest were drawn over the whole striatum, caudate, and putamen nucleus of each hemisphere on composite images of the 9 slices with the highest basal ganglia activity. The brain SPECT 99m Tc-TRODAT-1 imaging was compared with early-stage RLS patients and healthy volunteers groups. Result: SPECT imaging in RLS patients showed reduced radioactivity accumulation in the striatum profile. The major abnormal result observed is the significantly reduced uptake in striatal dopamine transporter density and activity. The symmetric striatal uptake was observed, and striatum dopamine transporter destiny was more impaired in patients with RLS disease. SPECT images also showed significant differences between patients and volunteers. Conclusions: This study supports that symptoms of restless legs resulted from the striatum of the brain dopaminergic system dysfunction.